Diskursus Anak Penderita Gangguan Jiwa Sebagai Korban Tindak Pidana Kekerasan Seksual Dalam Periskop Penegakan Hukum - Putry Alviani Reihan; Mohamad Rusdiyanto U Puluhulawa; Jufryanto Puluhulawa (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
Cases of sexual violence against children, especially those with mental disorders, are a serious problem that requires attention in law enforcement and child protection in Indonesia. In this context, the lack of regulations that specifically regulate the protection of children with mental disorders creates obstacles in handling cases and protecting victims. The problem raised in this research is: how is the law enforced for criminal acts of sexual violence committed against children with mental disorders and what efforts are made by investigators in this case to fulfill the rights of victims. This research is directed towards empirical legal research and the approach used in this research uses a statutory approach and a case approach. This research was carried out at Gorontalo Police. The results of the research and discussion explain that the law enforcement process for criminal acts of sexual violence against children who also experience mental disorders involves a series of steps that take into account the special conditions of the victims. Namely, the fulfillment of the victim's rights as a child with mental disorders, including: during the investigation and inquiry process the victim continues to be accompanied by P2TP2A, Social Services, psychologists and psychologists. This proves that the child is being looked after so that there is no trauma after the incident. In Indonesia there are no regulations that explicitly regulate this matter so investigators still use Article 81 paragraph 1 in conjunction with Article 76 e or Article 82 paragraph 1 in conjunction with Article 76 e of Republic of Indonesia Law No. 17 of 2016 concerning the Determination of Government Regulations in Lieu of Republic of Indonesia Law No. 1 of 2016 Regarding the 2nd Amendment to Republic of Indonesia Law No. 23 of 2002 concerning Child Protection into Law in conjunction with Article 64 paragraph 1 to 1 of the Criminal Code. With the general stages of the law enforcement process, namely, Reporting, Investigation, Examination of Victims, Collection of Evidence, Determination of Suspects, fingerprinting process, and then it is handed over to the prosecutor's office for the court process.